Quality of Context First International Workshop, QuaCon 2009, Stuttgart, Germany, June 25-26, 2009. Revised Papers - Rothermel, Kurt; Fritsch, Dieter; Blochinger, Wolfgang; Dürr, Frank (Computer Communication Networks and Telecommunications, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the first International Workshop on Quality of Context, QuaCon 2009, held in Stuttgart, Germany, in June 2009. The 11 revised papers presented were carefully reviewed and selected from 19 submissions and included in the volume together with 5 invited papers. Discussed are interdisciplinary approaches to context quality, such as models for degradation and consistency of context data, spatial ontologies and spatial data mining, trust in context data, methods and calculi for context quality assessment, frameworks and metrics for context quality, uncertainty in sensor data processing, quality-aware algorithms for context management, quality-aware event and stream processing, uncertainty in reasoning on context data, application-specific context quality and case studies, and visualization of context quality.